'1m fingerprint' data leak raises doubts over biometric security. (September 2019) - Unknown
Abstract : The discovery last month of up to 1 million fingerprint records plus facial images exposed on an open database has raised fears that biometric data is as vulnerable to hackers as traditional ID data if it is not stored securely.